Liquid-Liquid Extraction and Separation of Copper(II) and Nickel(II) Using LIX®984N - N. B. Devi (The Southern African Institute of Mining and Metallurgy, 2014)
The extraction of copper(II) from sulphate solution was investigated using LIX®984N in kerosene. The parameters that could affect the extraction, such as equilibrium pH, extractant concentration, salt concentration, various diluents, and temperature, were separately investigated. On the basis of slope analysis, the complex formed in the organic phase is proposed to be CuR2, where R is the anionic part of LIX®984N. The extraction equilibrium constant and Gibbs free energy ( G) of the extraction process were determined. The positive value of H obtained from temperature variation studies showed that the extraction process is endothermic. The extraction of copper was lowest when chloroform was used as the diluent. Separation and recovery of copper from a synthetic copper-nickel solution containing 6.35 g/L Cu(II) and 0.58 g/L Ni(II) was carried out using 20%(v/v) LIX® 984N. The separation factor ( = DCu/DNi) was found to be pH-dependent. A two-stage batch countercurrent extraction was carried out at an O:A ratio of 3:4 at equilibrium pH 1.05 for extraction of copper from copper-nickel solution, followed by copper stripping from the loaded organic phase with 15% H2SO4 at an O:A ratio of 3:1.